INTRA MUROS. ZUR GESCHICHTE DES (ERZWUNGENEN) SCHWEIGENS DER LITERATUR - Karolak, Czesław (Scripta Neophilologica Posnaniensia, 2019)
In the article, an attempt has been made to analyze the systems of control of social communication based on the history of censorship in Germany. Apart from the historical context, reference has been made to the relationship of systems of censorship to modernization processes. In addition, the crucial role of legal awareness in society has been indicated. Within the scope of the present analysis, important methodological issues concerning research on forms, manifestations and effects of censorship related to the XXth century German literature have been considered.